2009
DOI: 10.1177/1087054708326109
|View full text |Cite
|
Sign up to set email alerts
|

Improvement with Duloxetine in an Adult ADHD Patient

Abstract: Duloxetine could be an option for patients who either do not tolerate or show resistance to more common pharmacological choices. Randomized controlled trials are needed to assess the efficacy of duloxetine in treating ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…The first study that showed the effect of duloxetine on ADHD was a case report administering 60 mg/day duloxetine to a 53-year-old man with a recent diagnosis of ADHD. The results demonstrated a significant reduction in the Conners scale (30). Duloxetine has recently been reported to be useful in reducing ADHD symptoms in a 16-year-old girl with ADHD.…”
Section: Discussionmentioning
confidence: 83%
“…The first study that showed the effect of duloxetine on ADHD was a case report administering 60 mg/day duloxetine to a 53-year-old man with a recent diagnosis of ADHD. The results demonstrated a significant reduction in the Conners scale (30). Duloxetine has recently been reported to be useful in reducing ADHD symptoms in a 16-year-old girl with ADHD.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, duloxetine was not associated with any serious adverse effects. Improvements in ADHD symptoms have also been reported in an adult diagnosed with ADHD (Tourjman and Bilodeau, 2009). Tourjman and Bilodeau (2009) proposed duloxetine as a promising option in the treatment of adults with ADHD who do not respond to or develop side effects on the usual ADHD treatments.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, glutamatergic and dopaminergic signaling in the cortico‐striatal pathway appears to be important for effects of hyperactivity in DAT KO mice (Gainetdinov et al, 2001). There are some cases of adults with ADHD responding positively to duloxetine, a selective serotonin–norepinephrine reuptake inhibitor (SSNRI) (Tourjman & Bilodeau, 2009). However, currently, few studies have explored the effectiveness of SSRIs and other antidepressants in ADHD (Verbeeck, Tuinier, & Bekkering, 2009).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%